Rethinking Transformation and Its Knowledge(s): The Case of South African Higher Education - Lange, Lis (Critical Studies in Teaching and Learning, 2023)
The article argues that since the early days of the democratic transition in South Africa ’transformation’ as a concept has lost its intellectual, political and moral content through becoming institutionalised. In order to undo the institutionalisation of transformation, it is necessary to explore its relationship to two types of knowledge: knowledge for transformation and knowledge of transformation. The paper argues that transformation at higher education institutions needs to be seen in the interface between knowledge for and knowledge of transformation.